การปรับปรุงประสิทธิภาพในกระบวนการคัดแยกขยะรีไซเคิล - เบญจมาภรณ์ เลขะวณิช (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The study aims to improve the efficiency of recyclable wastes separated in the wooden pallet separation process (weight of 200 kilograms) and in the plastic separation process (weight of 360 kilograms) by Northern Art Product Co., Ltd. The study applies the motion and time technique. From an investigation of the recyclable waste separation process and supervisors’ interviews, there were many problems. First of all was the slow rate of separation process. As the layout of the separation line did not allow workers to move easily, workers readily felt tired, causing them to work more slowly. In addition, each machine part was not easily accessible. As a consequence of this, the production could not meet the customers’ demand. To improve the efficiency of the recyclable waste separation process, the researcher used the cause and effect diagram to analyze the problem. The flow diagram and the process chart were employed to investigate the movement of workers in the separation line as well as to design a new layout of the separation process. ECRS principle was then implemented to eliminate unproductive processes, led to simplified work procedures and shortened lead time. Finally, the speed of the recyclable waste separation process was compared before and after the improvement to find a solution to the problem. In conclusion, time used in the wooden pallet separation process (weight of 200 kilograms) decreased from 298.15 minutes to 238.59 minutes, reduced by 59.56 minutes, or a 19.98% reduction and the distance between processes reduced from 549 meters to 310 meters, decreased by 239 meters, or accounted to 43.53% In plastic separation process (weight of 360 kilograms), the speed decreased from 433.86 minutes to 390.60 minutes, reduced by 44.26 minutes, or a 10.18% reduction and the distance between processes reduced from 815 meters to 335 meters, decreased by 480 meters, or accounted to 58.89%